Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Di Sma Negeri 1 V Koto Kampung Dalam Kabupaten Padang Pariaman - Bur, Suhatri; Erniwati, Erniwati; Safardi, Safardi; Susanti, Erni (Universitas Sumatera Barat, 2024)
Employee job satisfaction is one of the important things in an organisation, so employees will try to give their best for the benefit of the company. The results of ASN job satisfaction in 2022 there are items, career development systems, education and training and HR information systems that show ASN dissatisfaction is a greater percentage than ASN job satisfaction. Judging from the existing phenomenon, it is known that problems regarding job satisfaction are still found in SMA Negeri 1 V Koto Kampung Dalam. This study aims to determine: The effect of transformational leadership and organisational culture on employee job satisfaction at SMANegeri 1 V Koto Kampung Dalam Padang Pariaman Regency with a sample of 71 people Data were collected by questionnaire and analysed with the SPSS program. Based on the results showed that transformational leadership affects employee job satisfaction of SMA 1 V Koto Kampung Dalam with a tcount of 2.586> t table 1.993 and a significance of 0.012 < 0.05. Organisational culture affects job satisfaction of SMA 1 V Koto Kampung Dalam employees with a tcount of 3.684 > t table 1.993 with a significance of 0.000 < 0.05. Transformational leadership and organisational culture simultaneously and significantly influence job satisfaction of SMA 1 V Koto Kampung Dalam employees with Fcount 30,818 and Adjusted R2 = 0.475 = 47.5%.